Initial Nutritional Assessment of Infants with Cleft Lip and/or Palate: Interventions and Return to Birth Weight. (March 2017) - Kaye, Alison; Thaete, Kristi; Snell, Audrey; Chesser, Connie; Goldak, Claudia; Huff, Helen
Objective: To assess and quantify cleft team practices with regard to nutritional support in the neonatal period Design: Retrospective review. Setting: Tertiary pediatric hospital. Patients: One hundred consecutive newborn patients with a diagnosis of cleft lip and/or cleft palate between 2009 and 2012. Main Outcome Measures: Birth weight, cleft type, initial cleft team weight measurements, initial feeding practices, recommended nutritional interventions, and follow-up nutritional assessments. Results: All patients in the study were evaluated by a registered dietitian and an occupational feeding therapist. Average birth weight and average age at the first cleft team visit were similar for each cleft type: cleft lip (CL), cleft lip and palate (CLP), and cleft palate (CP). The calculated age (in days) for return to birth weight was significantly different between cleft types: CL = 13.58 days, CLP = 15.88 days, and CP = 21.93 days. Exclusive use of breast milk was 50% for patients with CL, 30.3% for patients with CLP, and 21.4% for patients with CP. Detailed nutritional interventions were made for 31 patients at the first visit: two with CL, 14 with CLP, and 15 with CP. Conclusions: Distinct differences were seen in neonatal weight gain between cleft types. There was significantly greater total weight gain for patients with CL at their first visit and significantly slower return to birth weight for patients with isolated CP. Patients with CL required far fewer interventions at the initial assessment and were more likely to be provided breast milk exclusively or in combination with formula. Infants with CP were far less likely to receive any breast milk. Patients with CLP and CP required frequent nutritional interventions.